Estudo fitoquímico de Rhabdodendron amazonicum, Conchocarpus inopinatus e avaliação dos compostos isolados na inibição da fotossíntese - Sá, Israel Cívico Gil de (2010)
The Rhabdodendron amazonicum is a species of the monogeneric family Rhabdodendraceae, whose species are concentrated in the Amazon, Guianas and northern Bahia-Brazil. Phytochemical study of ethanolic extract of Rhabdodendron amazonicum leaves led to the isolation of a esterified steroid with cinnamic acid, the sitosteril cinnamate, two compounds of the class of ionone sesquiterpenes, Blumenol C and rhabdodendronlactona (unpublished). Another compound nor-ionone was identified via GC-MS analysis, selecting the chromatogram peak corresponding to ion m/z 208, which was identified as 1,5,5-trimethyl-6β-hydroxy-6-but-2-enyl-cyclohexa-1-ene-3- one. The identification of this compound reinforce the proposed biogenesis for rhabdodendronlactona from Blumenol C. Phytochemical study of methanolic extract of stem Conchocarpus inopinatus led to the isolation of three alkaloids: one acridones (methylarborinine), one quinolones (1-methyl-2-phenyl-4- quinolone) and one furoquinoline (dictamnine) and two coumarins, the marmesin and scopoletin. All substances, except for scopoletin were submitted to the inhibition tests of electron transport basal, phosphorylating and uncoupled. But only the marmesin showed inhibitory activity in the basal and uncoupled electron transport. Through measures of chlorophyll fluorescence, analyzing the parameters related to transient OJIP, could suggest the marmesin action in the pool of quinones, inhibiting the transport of electrons from this region. However, to confirm this mechanism of action would require the implementation of other partial reactions involving donors and acceptors of electrons, which were not possible due to the low quantity of isolated compound.